Teaching English to Second-Grade Dyslexia-Prone Students: Perspectives of Y-Generation Parents on Foreign Language Learning in Elementary School - Alexandra, Natasha Filya; Artini, Luh Putu; Ana, I Ketut Trika Adi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The aim of this research is to describe the knowledge from parents of the second-grade elementary school students who potentially dyslexic and to describe how parents support their second-grade elementary school children who potentially dyslexic in learning English. This research was conducted using qualitative methods in the form of a case study. Data collection was carried out using interview and observation. The findings showed that none of the parents had prior knowledge of dyslexia, although they were aware of their children’s difficulties that were attributed to dyslexia. Parents expressed frustration in teaching their children, often yelling or ignoring their children. Two of the Y-Generation parents in the study used YouTube and flashcards to teach, but one parent simply used her knowledge. These results highlight the need for educational programs to increase parents’ awareness of dyslexia and improve their teaching strategies. Strengthening collaboration between parents and educators is essential to fostering inclusive learning environments that enhance the literacy skills of children who are potentially dyslexic.